Corrosion inhibition of mild steel using novel pyridine derivative in 1 M hydrochloric acid - Al-Amiery, A.A.; Shaker, L.M. (Korose a ochrana materiálu, 2020)
A novel pyridine derivative was synthesized, and its corrosion inhibition effects on mild steel in a 1M hydrochloric acid environment were investigated by gravimetric techniques, The results demonstrated that the inhibitive performance increased with the increasing of inhibitor concentration. At 303, the inhibition efficiency of pyridine derivative 4-hydroxy-3-(pyridin-2-ylaminomethyl)toluene accomplished 96.2% at the inhibitor concentration of 0.005 M. The mechanism of inhibition implicated the forming of a protective layer from inhibitor molecules on the surface of mild steel by a Langmuir adsorption isotherm. The presence of nitrogen and oxygen atoms in the structure of 4-hydroxy-3-(pyridin-2-ylaminomethyl)toluene confirmed by CHN-analysis revealed the adsorption of inhibitor molecules on the surface of mild steel surface.